Postural balance strategies for experienced rhythmic gymnasts in two-legged stands - L. A. Konovalova; R. Vasiljev; L. G. Lysenko (Спортивная медицина: наука и практика, 2023)
Objective: The purpose of this study was to find out the indicators of the distribution of plantar pressure in the two-legged stands with open and closed eyes in experienced rhythmic gymnasts.Materials and methods: 31 highly qualified gymnasts (candidates and masters of sports of Russia), age 18.5 ± 0.5 years, experience in rhythmic gymnastics 13.5 ± 1.5, performed three upright postures on the footscan ® podometric platform of RSscan: the main stand, a modified Romberg test with open and closed eyes. Postural control was assessed by quantifying the plantar pressure (P%) in relation to 4 zones of the right and left foot and the trajectory of the movement of the center of pressure (CP) over time intervals.Results: The results of the study showed the presence of a right-sided distribution of plantar pressure in two-legged stands in experienced gymnasts. The regulation of posture occurs mainly in the anterior-posterior direction, but has different strategies for managing balance. The sagittal-cross pattern determines the interaction of plantar pressure between the right and left feet in the basic pose. The Romberg test with open eyes (EO) and closed eyes (EC) characterizes sagittal-parallel and sagittal-asymmetric balance, respectively. We revealed an increase in the vibrations of the gymnast's body in the absence of visual information for only the first 12 seconds.Conclusions: We have identified a variety of combinations of two types of strategies while maintaining posture in simple poses. This indicates the ability of experienced gymnasts to fine-tune the postural stability, including in the absence of visual information.